Agriculture and climate change: The importance of property rights in climate change mitigation - Markelova, Helen; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2009)
Even with abundant evidence of the urgent need for action on climate change mitigation, there are still those who consider mitigation strategies a burden. In the agricultural sector, climate change mitigation calls for changing some agricultural and resource management practices and technologies and often requires additional investment. However, there is an opportunity in agriculture for net benefit streams from a variety of zero- or low-cost mitigation opportunities ranging from agroforestry practices and restoration of degraded soils to zero-till and other land-management practices. Momentum has been generated to incorporate agriculture into carbon markets, potentially allowing smallholder farmers to access benefit streams from such transactions. However, who will receive the benefits from mitigation funds by, for example, increasing carbon stocks or reducing greenhouse gas (GHG) emissions from land, will depend on the way different types of property rights are defined and dealt with in the upcoming climate change negotiations in Copenhagen. In many areas of the world, land tenure arrangements are complex. For example, in Africa, more than 90 percent of the land is formally claimed as state land, although millions of farming and pastoralist households use various customary and informal arrangements to access the land and other resources. Millions of hectares of forest and pastoral land in Asia and Latin America are similarly listed as state land, although used by communities, especially those of indigenous people or other marginalized ethnic groups. Often the same area may be under co-existing informal tenure systems, most of which are not recognized by formal land laws, but are instead accepted and enforced by the communities. Even where property rights are vested in a formal legal system with strong enforcement procedures, climate change mitigation measures raise new issues of who owns incremental carbon stocks and who should receive compensation for reductions in GHG emissions.